Secret empire : Eisenhower, the CIA, and the hidden story of America's space espionage - Taubman, Philip (Simon & Schuster, 2003)
"In a brief period of explosive, top-secret innovation during the 1950s, a small group of scientists, engineers, businessmen, and government officials rewrote the book on airplane design and led the nation into outer space. In an effort no less audacious than the creation of the atomic bomb, they designed, built, and operated the U-2 and supersonic SR-71 spy planes and Corona, the first reconnaissance satellites - machines that could collect more information about the Soviet Union's weapons in a day than an army of spies could assemble in a decade." "Their remarkable inventions and daring missions made possible arms control agreements with Moscow that helped keep the peace during the cold war, as well as the space-based reconnaissance, mapping, communications, and targeting systems used by America's armed forces in the Gulf War and most recently in Afghanistan